Penyelesaian Sengketa Ekonomi Syariâah Sebagai Sebuah Kewenangan Baru Peradilan Agama - KaÃ¢Â€Â™bah, Rifyal (Islamic University of Indonesia, 2007)
Islamic law as a living law in Indonesia has developed in dependence era. The developing of Islamic law indicates for example in term of Islamic court jurisdiction. Islamic court decision departing from fiqh, and its execution should be supported by statecourt. The judges of Islamic court educate based on traditional Syariahand they do not educate based on secular law. Besides, Islamic court organization does not under supreme court. One of the changing of Islamic court recently is enlarging its jurisdiction according to Act No. 3 year 2006 in particular regarding the handling of Islamic Economics cases in Indonesia. The following article tries to investigate the changing and the challenging of Islamic court as one of modern Indonesia for the future. Kata kunci: Sengketa, kewenangan, ekonomi Syariâah, peradilan agama, Indonesia.